Characteristics of Individuals and Workplace Conditions with Job Satisfaction Lecturer Health Polytechnic of Aceh - Salfiyadi, Teuku (Jurnal Ilmiah Peuradeun, 2017)
As an organization that produces health services, one of the factors that determine the quality of product is personnel who worked with dedication and professionalism. This is achieved when the manager is able to give a satisfaction to all employees on the job. This study aimed to investigate the relationship individual and workplace characteristics with job satisfaction of employee. The populations of study were 32 employees of Environmental Health Department of Health Polytechnic of Aceh. Individual and workplace characteristic and job satisfaction were collecting by structural questionnaires. The product moment correlation was conducted to analysis of the data. The study showed individual and workplace characteristics were strongly correlation on job satisfaction (p=0.000 and r = 0.805) or 80.5% the independent variables are able to explain the dependent variable of job satisfaction is r-square = 0.647, or by 64.7%.